Two countable, biconnected, not widely connected Hausdroff spaces - V. Tzannes (International Journal of Mathematics and Mathematical Sciences)
We construct two countable, biconnected spaces, not widely connected, not having a dispersion point, and not being strongly connected. The first is Hausdorff and the second is Urysohn and almost regular.